2015
DOI: 10.1103/physreve.91.042918
|View full text |Cite
|
Sign up to set email alerts
|

Analytical stability boundaries of an injected two-polarization semiconductor laser

Abstract: The classical problem of a semiconductor laser subject to polarized injection is revisited. From the laser rate equations for the transverse electric (TE) and transverse magnetic (TM) modes, we first determine the steady states. We then investigate their linear stability properties and derive analytical expressions for the steady, saddle-node, and Hopf bifurcation points. We highlight conditions for bistability between pure- and mixed-mode steady states for the laser subject to either TE or TM injection. To ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(44 reference statements)
3
18
0
Order By: Relevance
“…This is an unusual situation because optical injection in the polarization with smaller optical losses causes emission in the polarization with larger losses [19]. Very recently a linear stability analysis of the mixed-mode steady states of an optically injected twopolarization modes edge-emitting semiconductor laser has been performed [20]. Dynamical evolution of mixed-mode steady states and IL+PS states is similar for VCSELs for which the spin dynamics can be adiabatically eliminated [19], and so the linear stability analysis of [20] was successfully extended to the VCSEL case [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is an unusual situation because optical injection in the polarization with smaller optical losses causes emission in the polarization with larger losses [19]. Very recently a linear stability analysis of the mixed-mode steady states of an optically injected twopolarization modes edge-emitting semiconductor laser has been performed [20]. Dynamical evolution of mixed-mode steady states and IL+PS states is similar for VCSELs for which the spin dynamics can be adiabatically eliminated [19], and so the linear stability analysis of [20] was successfully extended to the VCSEL case [19].…”
Section: Introductionmentioning
confidence: 99%
“…We will term this situation as IL+PS. This corresponds to the experimental observation in VCSELs of the mixed-mode steady states predicted in [27]. We obtain analytical expressions for the power of both linear polarizations in the IL+PS state.…”
Section: Pm2 or Bosamentioning
confidence: 99%
“…Studies of PS in VCSELs subject to parallel optical injection, in which the directions of the linearly polarized light from the master laser and the slave VCSEL are parallel, are scarce: just a couple of experimental works have reported PS in VCSELs under these circumstances [21][22]. An analytical study of an optically injected twopolarization modes semiconductor laser has recently shown that pure and mixed-mode steady states can coexist [27]. Linear stability techniques have been used to analyze bistability between pure-and mixed-mode steady states [27].…”
Section: Pm2 or Bosamentioning
confidence: 99%
See 1 more Smart Citation
“…Other feedback scenarios have included polarization rotated feedback where the polarization of the feedback light is rotated relative to the dominant polarization mode of the laser light [7,8,9]. Recently, the effects of injection on the stability properties 20 from two polarization modes has been studied [10].…”
Section: Introductionmentioning
confidence: 99%